Implementation of the Responsibility to Protect Principle in the Prevention of Genocide in Indonesia - Khairuddin Tampubolon; Muhamad Hendry Surya (Universitas Medan Area, 2026)
This study aims to analyze the implementation of the Responsibility to Protect (R2P) principle in the context of genocide prevention. Using a qualitative method based on literature study, this study examines national legal documents such as the Human Rights Law, the Social Conflict Handling Law, and Indonesia's diplomatic statements in UN forums related to R2P. Data were analyzed using Miles and Huberman's interactive models to identify the fit between R2P standards and Indonesian policy instruments. The results show that Indonesia supports R2P normatively, especially in Pillar 1 which emphasizes the state's responsibility to protect citizens from mass violence. However, this support is ambivalent because the state still rejects Pillar 3 which opens up the possibility of international collective intervention. A national policy analysis revealed that Indonesian legal instruments have contained elements of protection, but are not specifically designed to prevent genocide, so their implementation is more reactive than preventive. The Papuan case study shows that there is a risk of structural genocide that has not been officially recognized by the state. The main obstacles to the implementation of R2P in Indonesia lie in the dominant security paradigm, the absence of a human rights-based early warning system, and the politics of denial of the potential for mass violence. This study recommends the explicit integration of R2P principles into national policies, the establishment of early warning systems, and the reorientation of security approaches to human security. In conclusion, Indonesia is at the stage of R2P as a discourse, but it has not fully become R2P as a policy practice.